ANALISIS RASIO KEMANDIRIAN DAN EFEKTIFITAS KEUANGAN DAERAH DI KABUPATEN BERAU: ANALISIS RASIO KEMANDIRIAN DAN EFEKTIFITAS KEUANGAN DAERAH DI KABUPATEN BERAU - Merlin, Merlin (ECO-BUILD, 2025)
The purpose of this study was to determine the level of independence ratio and regional financial effectiveness in Berau Regency. The method used is a quantitative method or data obtained in the form of numbers. The results showed that from 2017 to 2021 an average of 10.33% was obtained. This shows that the local government of Berau Regency is still in the very low category. The ratio of regional financial effectiveness in Berau Regency in 2017-2021 shows an average percentage of 111.62%. this shows that the local government of Berau district is in the very effective category.